Modelling the community support for seniors. The case studies in low- and middle-income countries - Gawron, Grzegorz (Research Papers of Wrocław University of Economics, 2018)
In 2014 WHO issued a call for preparing case studies on community-based initiatives that support older people in low- and middle-income countries. Finally, seven case studies were completed with one cancellation. The main objective for this article is to match the selected initiatives to available in the literature five main theoretical models of social support. They will be used as a theoretical basis for the analysis. It seems very interesting if studied initiatives that operate in different conditions of social and cultural development will implement similar or different mechanisms of social support for seniors and whether it will be possible to assign these initiatives to one of the previously described models
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 32-48
Keywords: aging; social support; models of social support; low- and middle-income countries; starzenie; wsparcie społeczne; modele wsparcia społecznego; krajeo niskich i średnich dochodach